2008
DOI: 10.1111/j.1467-8683.2008.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit Committee, Underpricing of IPOs, and Accuracy of Management Earnings Forecasts

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: This paper examines the role of audit committees (AC) in the initial public offering (IPO) process in a governance environment where AC best practices are well established but their adoption is voluntary. We consider the creation and characteristics of the committee as signals that issuing firms can use to reduce the underpricing often associated with IPOs. We also examine the effect of the committee on the quality of management earnings forecasts included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 66 publications
6
88
2
Order By: Relevance
“…Consistent with prior evidence, control variables of company size and forecast horizon are found to have a significant positive association with absolute forecast error [6], [8], [14], [23], [30], [31]. Company age on the other hand is found to have a positive association with absolute forecast error while there is no significant association is documented between leverage and absolute forecast error.…”
Section: Resultssupporting
confidence: 77%
“…Consistent with prior evidence, control variables of company size and forecast horizon are found to have a significant positive association with absolute forecast error [6], [8], [14], [23], [30], [31]. Company age on the other hand is found to have a positive association with absolute forecast error while there is no significant association is documented between leverage and absolute forecast error.…”
Section: Resultssupporting
confidence: 77%
“…Recently, Chan and Li (2008) find that audit committees with high governance quality are associated with higher firm value. Bedard, Coulombe and Courteau (2008) find that audit committee governance quality is inversely related to the level of initial public offering underpricing. Similarly, if high corporate governance quality of compensation committees can improve the monitoring effectiveness of compensation committees, then executive compensation contracts will be designed and implemented to better align the incentives of agents with the interests of principals.…”
Section: Background and Hypothesismentioning
confidence: 99%
“…Finally, the study of Bédard, Coulombe, and Courteau () exploits the choice by Canadian IPOs to voluntarily create an audit committee. They find that the creation of a committee has no effect on underpricing, but if its members are independent and have expertise in financial matters, it decreases underpricing significantly.…”
Section: Signaling In Iposmentioning
confidence: 99%
“…Bédard et al () examine the role of audit committees in Quebec during a period when the creation of the audit committee and the related disclosures were voluntary. As discussed above, they found that the audit committee (AC) is a credible signal of quality for IPOs, and it is associated with lower underpricing when the committee is composed of a majority of independent members and includes at least one financial expert.…”
Section: Corporate Governance (Cg) and Ipo Researchmentioning
confidence: 99%